The World Book Encyclopedia (W-X-Y-Z, Vol.21) - World Book Inc. (Chicago World Book Inc., 2000)
An encyclopedia designed especially to meet the needs of elementary, junior high, and senior high school students
Include Map and color Illustration
Keywords: Encyclopedias and dictionaries -- Encyclopedias